Bending Properties of Elephant Grass Fiber Reinforced Epoxy Resin Composites - Alwiyah Nurhayati (Journal of Natural Sciences and Mathematics Research, 2015)
Elephant grass fiber reinforced epoxy resin composites has been made and characterized on its mechanical properties that is bending properties. The specimen made by varying its filler’s volume fraction. The elephant grass fiber  treated by immersing in water for 3 days continued by beating the strips gently in order to loosen and separate the fiber and scrapped with sharp knife and combed until individual fibers were obtained and cut uniformly in 2 cm length and 1 mm diameter width average. Hand lay up process used to prepare the composite specimens with 1%,  3% and 5% volume fraction. This method is the simplest method and require a low cost. The dimensions of the specimens used to carry out the test adapted from ASTM D 3379-75 for Bend testing. The results showed that filler volume fraction has effect to its bending strength. Specimen with 1% filler volume fraction has the highest bending stress whereas 5% filler volume fraction specimen has the highest elasticity modulus value.